LOCAL TREATMENT OF PURULENT WOUNDS BY USE OF BANDAGE WITH STELLANIN-PEG 3% - V. N. Chernov; A. V. Rodakov; R. N. Bayramov (Медицинский вестник Юга России, 2013)
Purpose: to improve the results of treatment of patients with purulent wounds by use of bandages with “Stellanin-PEG 3%”.Materials and methods: the research groups included 55 patients with purulent wounds of different origin, local treatment which apply ointment «Levomekol′ or «Stellanin-PEG 3%». To assess the effectiveness of the treatment we used vulnografy with the measurement area and the volume of the wound, cytology of the center and the edges of the wound, bacteriology at 1, 5 and 10 days.Results: when you use the ointment «Stellanin-PEG 3%» decline in terms of healing the wounds, surgical complications and length of stay in the hospital until 2 bed-days.Summary: a rapid decline in the number of microorganisms in the wound in treatment of Stellanin, plays a very important role in the healing process of wounds festering.